Modification of the Algorithm for Selecting a Variable Parameter of the Gaussian Interpolation Function - Sidorenko, Iu.V.; Gorodetsky, M.V. (Control systems & computers, 2020)
The paper presents an algorithm for selecting the optimal value of the variable parameter α of the Gaussian interpolation function to obtain the smallest possible error when interpolating the tabular data. The results of the algorithm are checked on a sample of elementary mathematical functions. For comparison, the interpolation data of the Lagrange polynomial are given. The paper presents the results of Gaussian interpolation at different α, conclusions are made about the need to applying the algorithm for selecting of its optimal value. Метою дослідження є зменшення похибки Гаус-інтерполяції за рахунок побудови алгоритму автоматичного підбору варіативного параметра α та створення програмного забезпечення для вивчення властивостей методів Гаус-інтерполяції. Результати. На основі аналізу роботи методів Гауса було побудовано модифікований алгоритм розрахунку оптимального значення варіативного параметра α, наводяться результати Гаус-інтерполяції при різних α, зроблено висновки щодо необхідності застосування алгоритму в залежності від умов поставленої задачі. В статье приводится алгоритм выбора оптимального значения вариативного параметра α интерполяционной функции Гаусса для получения наименьшей погрешности при интерполяции табличных данных. Результаты работы алгоритма проверяются на выборке элементарных математических функций. Для сравнения приводятся данные интерполяции полиномом Лагранжа. В работе приводятся результаты Гаусс-интерполяции при различных α, сделаны выводы о необходимости применения алгоритма выбора его оптимального значения.